REKONSTRUKSI TEORI KOMUNIKASI DALAM MENGHADAPI DISINFORMASI DIGITAL: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Heri Wahyudi Marpaung; Mailin (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to: 1) identify the development of communication theory in the context of digital disinformation; 2) analyze the limitations of classical communication theory in explaining the phenomenon of algorithm-based communication; and 3) formulate a framework for reconstructing communication theory that is more adaptive to contemporary challenges. The study uses a qualitative approach with the Systematic Literature Review (SLR) method based on the PRISMA protocol for indexed articles from 2015–2024. The analysis is conducted through a thematic approach to map conceptual transformations in digital communication studies. The results of the study indicate that: 1) A paradigm shift from linear communication to multidirectional and decentralized networked communication; 2) Classical communication theories such as agenda setting, Two-step flow, and the spiral of silence have limitations because they have not integrated the role of algorithms, platforms, and non-human actors in the communication process; and 3) A framework for reconstructing communication theory that is based on three main principles: network communication, the integration of algorithms as non-human communication actors, and strengthening digital literacy. The resulting model includes four main components: human actors, algorithmic actors, platform structures, and socio-political contexts that interact in shaping the circulation of digital information. This reconstruction is expected to enrich the development of digital communication theory and serve as a conceptual basis for mitigating disinformation in the era of platformization and artificial intelligence.